Three new species of Leptohyphidae (Insecta: Ephemeroptera) from Central Amazon, Brazil - Belmont, Enide Luciana L.; Salles, Frederico F.; Hamada, Neusa (Zootaxa, 2011)
Three new species of Leptohyphidae are described based on adults and/or nymphs collected in Manaus (Reserva Florestal Adolpho Ducke) and Presidente Figueiredo municipality: Tricorythodes faeculopsis sp. nov., Tricorythopsis acara sp. nov. and T. intercalatus sp. nov. With this work, the number of Leptohyphidae in Brazil increases from 35 to 38 species.